(Macrolides –Lincosamides - Streptogramins) and Vancomycin Resistance Phenotypes of Staphylococcus aureus Isolated From Clinical Samples by Using Vitek 2 Compact System - Mohammed , Luma S.; Flayyih , May T.; Flayyih , May T. (Iraqi Journal of Science, 2022)
The study was carried out to investigate MLS and vancomycin resistance phenotypes in S.aureus isolated from different clinical samples .A total of 40 of S.aureus isolated from Baghdad hospitals from different clinical samples such as blood , urin, sputum ,skin and ear swabs used to identified MLS and vancomycin resistance phenotypes.The susceptibility pattern showed that 3 islolates (7.5) % constitutive resistance to erythromycin ,clindamycin and streptogramins (cMLS) while 9 isolates (22.5)% gave inducible resistance to erythromycin ,clindamycin and streptogramins (iMLS) , 10 isolates (25)% showed resistance to erythromycin and sensitive to clindamycin (M phenotype) and 18 isolates (45)% of S.aureus isolates had resistance phenotype to streptogramin A and B (SAB). (5)% of S.aureus isolates had resistance to vancomycin (VRSA) (85)% of isolates were vancomycin sensitive (VSSA) and (10)% of S.aureus isolates had intermediate resistance to vancomycin (VISA) with heterogeneously VISA phenotype (hetero-VISA or h-VISA).